PENGARUH ASSOCIATIVE PLAY TERHADAP TINGKAT STRESS PADA ANAK USIA 3-5 TAHUN - Pravitasari, Ines Ratni; Setyaraini, Didien Ika; Triningsih, Reni Wahyu (Jurnal Informasi Kesehatan Indonesia (JIKI), 2019)
The Phenomenon of fear more experienced by the child during pre-school than any other time. Continual fear will cause stress. This study aims to determine the effect of associative play on stress levels in children aged 3-5 years. The methods used was quasy-experimental design with one grup pre test post test approach. Large sample is 25 students who experience stress. The research instrument was the School Anxiety Scale-Teacher Report (SAS-TR) questionnaire sheet. The results showed the stress level of children aged 3-5 years before associative play, namely the majority of respondents (52%) experienced moderate stress and after associative play experienced mild stress (60%). The results of the study were analyzed using the Wilcoxon Signed Rank Test with dan = 0.05 and showed the value of r value = 0,000 so that r value < H0, then H0 was rejected which means that there was an associative play effect on stress levels in children aged 3-5 years.